Retrospective analysis of pediatric sepsis and the burden of antimicrobial resistance in Duhok, Kurdistan Region of Iraq - Ibrahim, Delveen R.; Saadi, Abdulrhaman T.; Yahya, Nizar B.; Ibrahim, Marwa S.; Saeed, Ali Y.; Abdulaziz, Sawsan S.; Hasqyal, Revan Y.; Alarsalani, Berivan K.; Ibrahim, Khalid S. (Frontiers in Pharmacology, 2024)
Introduction: Sepsis is a life-threatening complication in pediatric patients. This study primarily aimed to investigate sepsis-causing bacteria and their antimicrobial resistance profile and check the change in the antimicrobial resistance trend for some selected bacteria. In addition, we evaluated the incidence of sepsis, the related mortality rate, and the effectiveness and outcome of the treatment regimes in sepsis pediatric patients. Methods: A retrospective analysis was conducted on 4-year data (2018–2021) collected from three intensive care units at the Hevi Pediatric Teaching Hospital. Sepsis screening involved clinical detection and confirmation by blood culture. Results: A total of 520 out of 1,098 (47.35%) blood samples showed positive microbial growth. A decrease in sepsis rate was observed during the COVID-19 pandemic. Coagulase-negative Staphylococci (CoNS) and Klebsiella pneumonia were the most commonly isolated bacteria. A notable variation in the antimicrobial resistance trend was observed among sepsis-causing bacteria. The empirical sepsis treatment recommended by the WHO was ineffective, as certain bacteria exhibited 100% resistance to every antibiotic tested. The mortality rate significantly increased from 1.3% in 2018 to 16.5% in 2021. Discussion: The antimicrobial resistance profile of sepsis causing bacteria is of concerns, indicating a potentially serious situation. Thus, to avoid treatment failure, the monitoring of antimicrobial resistance in pediatric patients is essential.